Enpostil Lowers Elevated Serum Gastrin Concentrations in Patients with Pernicious Anemia - P Kirdeikis; M Mant; L Zuk; D Fisher; L Bynum; ABR Thomson (Canadian Journal of Gastroenterology)
A double-blind, randomized, crossover, placebo controlled study of Latin square design was conducted to determine the gastrin-lowering effects of a synthetic orally administered prostaglandin, enprostil, in fasted and fed patients with hypergastrinemia due to pernicious anemia. The study subjects were one male and six female patients between the ages of 39 and 76 years with known pernicious anemia and elevated serum gastrin concentrations. In random order patients received twice daily enprostil 350 μg bid, enprostil 700 μg bid and placebo for one week, with a one week washout between treatment phases. Measurements of serum gastrin were performed in the fasting and postprandial states prior to dosing, at the end of each treatment phase, and at the end of each washout phase. Enprostil 350 μg bid lowered elevated fasting gastrin concentrations, and both doses of enprostil lowered the food-stimulated increases in serum gastrin. When changes in food-stimulated gastrin concentrations were adjusted for pre-meal gasrrin concentrations, there was a consistent dose response between placebo, 350 and 700 μg enprostil bid. All patients experienced adverse events while on enprostil, particularly on the higher dose; nausea, vomiting, diarrhea and abdominal pain we re reported most frequently. Thus, enprostil reduced basal and food-stimulated gastrin release in seven patients with pernicious anemia. The mechanism of this effect remains to be established, but it is clearly independent of an effect on acid secretion.